Memahami Kecanduan Game Online Melalui Pendekatan Neurobiologi - Lutfiwati, Sri (Universitas Islam Negeri Raden Intan Lampung, 2018)
Playing online games is an alternative of entertainment that is fairly easy to obtain and inexpensive when compared to other entertainment modes. The behavior of playing online games is preferred because it offers various benefits for the players both mentally and materially. Behind the positive benefits obtained, excessive online gaming results in the emergence of addiction with some negative effects, such as the emergence of aggression behavior, loss of interest to engage in the real world, decreased cognitive abilities and lack of self regulation. This research aims to understand the process of online game addiction through a neurobiology approach using literacy study methods. The conclusion in this study is that if online gaming behavior continues to be repeated and accustomed, the dopaminergic pathway in the brain will strengthen and settle, causing addiction, which will eventually strengthen the reactive system and weaken the reflective system so the cognitive abilities decreased and are difficult in controlling their self control. The precaution that parents and educators can make a duration limit in playing online games, recognizing the details of the game to find out the warning sign if their child starts to cross the line approaching the level of addiction. Corrective actions that can be done by counselors and therapists should be focused on the factors that trigger the emergence of addiction in an effective way.